Microfluidic chip-assisted separation process and post-chip microalgae cultivation for carotenoid production - Karacaoglu, Beyza; Kocer, Anil Tevfik; Inan, Benan; Butun, Ismail; Mercimek, Rabia; Ghorbani, Morteza; Kosar, Ali; Balkanli, Didem (SPRINGER, 2025)
In many fields of biotechnology, pure microalgae cultures isolated from mixed cultures that exist in nature are needed as raw material sources for the production of high-quality products such as nutraceuticals, cosmetics and biofuels. Regarding the isolation of microalgae, microfluidic systems have gained popularity in recent years due to their low energy and chemical requirements for rapid and effective separation. In this study, optimum flow rates were determined using spiral microfluidics for the separation of microalgae from bacteria, followed by the cultivation of separated microalgae. Then the microalgae obtained in the green phase were subjected to nutrient stress to induce carotenoid production. Carotenoids were extracted after 30-day cultivation, and characterization analyses were performed. Subsequently, the SuperPro Designer (R) software was used to determine the potential for large-scale carotenoid production from Chlorella minutissima. The experiments showed that the fabricated microfluidic system achieved a separation yield and purity of 84.9% and 93.8%, respectively. Furthermore, a 2.5-fold increase in growth rate and carbohydrate and an approximately 1.3-fold increase in protein, lipid, and pigment contents were observed in the post-chip culture. Additionally, a 170% increase in carotenoids was observed within 20 days after induction with nutrient stress. Also, it was shown that microalgal carotenoids could be produced in large scale from C. minutissima by recultivating post-chip microalgae and subjecting them to nutrient stress. This study considered multiple flow rates in microchannels designed to separate microalgae from bacteria and carotenoid production from sorted microalgae for the first time.
Keywords: Chlorella; Microfluidic technology; Inertial microfluidics; Bioprocess; Carotenoids; HAEMATOCOCCUS-PLUVIALIS; LIPID EXTRACTION; ASTAXANTHIN; LIGHT; BIOTECHNOLOGY; CULTURES; GROWTH; DEVICE; ALGA; Biotechnology & Applied Microbiology; Marine & Freshwater Biology